Pathway-based network medicine identifies novel natural products for Alzheimer’s disease - Yumei Liang; Siqi Xie; Jianping Jia (Alzheimer’s Research & Therapy)
Abstract Background Alzheimer’s disease (AD) is the leading cause of dementia, characterized by a complex pathogenesis that complicates the development of effective treatments. Natural products are promising multitarget agents because of their ability to interact with multiple molecular targets. Network-based medicine presents a robust strategy for discovering such agents, which can address the intricate mechanisms underlying AD. Methods In this study, we constructed an AD-related pathway-gene network via text mining and pathway database construction. This network facilitated the identification of natural products that target multiple pathways and genes associated with AD. We evaluated the safety profiles of two selected natural products in C57BL/6J mice through assessments of general behavior, body weight changes, vital organ weight and morphology, and hematological and biochemical parameters. APP/PS1 transgenic mice were subsequently treated with these natural products—either individually or in combination—to assess their therapeutic effects. Cognitive function was evaluated via behavioral tests, such as novel object recognition, Y-maze, and Morris water maze tests. Additionally, immunohistochemical staining and enzyme-linked immunosorbent assays were performed to examine Aβ-associated pathological changes. Transcriptomic analysis and quantitative real-time polymerase chain reaction (qRT-PCR) were employed to elucidate the mechanisms underlying the effects of the natural products. Results The constructed AD-related pathway-gene network encompassed three perspectives: (i) Most Studied Pathways (21 pathways with 5325 genes), (ii) Gene-Associated Pathways (26 pathways with 2557 genes), and (iii) Popular Pathways (24 pathways with 3435 genes). Two natural products, (-)-Vestitol and Salviolone, were selected for further validation. Their safety was confirmed in C57BL/6J mice. Notably, the combination of (-)-Vestitol and Salviolone synergistically affected cognitive function in APP/PS1 transgenic mice by reducing Aβ deposition and lowering toxic soluble Aβ levels in the brain. Transcriptomic analysis and qRT-PCR experiments revealed that their combination regulated AD-related pathways and genes more comprehensively, particularly affecting the Neuroactive ligand-receptor interaction and Calcium signaling pathway. Conclusions Our findings demonstrate that screening potential natural products through an AD-related pathway-gene network is a promising strategy for discovering novel therapeutics for AD. The therapeutic potential of (-)-Vestitol and Salviolone as novel candidates for AD treatment is underscored by their synergistic effects, attributed to their comprehensive regulation of AD-associated pathways and genes.